Creativity Products of the Calung Al-Khoir Pagongan Tegal Music Group in the Song Arrangement Process - Nurjanah, Putri Eka; Rizki Harmono Sejati, Irfanda (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2023)
This article aims to find out the product results of the creativity of the Calung Al-Khoir Pagongan Tegal music group in creating a new arrangement of an existing song as well as the process of practicing the Calung Al-Khoir Pagongan Tegal music group. This writing is qualitative writing with the writing location in Grogol Village, Dukuhturi District, Tegal Regency, namely the Al-khoir Pagongan calung music group. The Al-khoir Pagongan calung music group, located in Grogol Village, Dukuhturi District, Tegal Regency, is one of the calung music groups that actively performs in the city of Tegal. This music group, which was formed in 2018, operates through an agreement between young people to fill their free time which is then used as a means of earning a living besides their main job. The Al-Khoir music group is a Calung music group that performs songs with the characteristics of Calung Banyumasan. Data collection techniques were carried out using observation, interviews, and documentation with sources. Data analysis is obtained from reduction, data presentation, and concluding. This article was also written using a musicological approach. The focus of this writing problem is creativity in arranging songs and the process of practicing the Calung Al-Khoir music group. The results of this writing show that the creative product produced by the Al-khoir Pagongan calung music group is in the process of practicing, making arrangements, costumes during performances, and the concept of appearance at each different event. This writing concludes that the Calung Al-koir Pagongan Tegal Music Group produces creative products, namely song arrangements, costumes when performing, different formations of musicians at each different event, as well as their performance concept which carries the calung Banyumasan concept.